IMC in an emerging economy: the Chinese perspective. Issue 2 (3rd March 2016) - Schultz, Don; Chu, Guangzhi; Zhao, Beryl
Abstract : Integrated marketing communications (IMC) planning and implementation vary greatly by market and country. This study, based on the survey data compiled from 135 Chinese marketing executives, focuses on IMC in China's emerging economy, with the goal of providing an outlook of IMC's current development in China while uncovering factors in the country's socioeconomic and business infrastructures that may cause IMC to deviate from the traditional Western model. The study also explores Chinese responses to the rising proliferation of digital media and its implications for IMC development. The study concludes that despite uneven business development and a current lack of training in IMC-related skills, IMC appears to be the inevitable course or the future of Chinese marketing communications. Due to factors unique to the Chinese business landscape, such as government-owned business structures, political nuances in marketing channel relationships, and uneven development of consumer culture, IMC in China will likely evolve differently than in the US. Survey respondents reveal that IMC is progressing much faster in local, privately owned firms than in their state-owned counterparts. The rise of digital media will also disrupt traditional media outlets, providing challenges to the Chinese marketer.